(untitled) (Herald of the National Children’s Medical Center, 2022)
Sensorineural hearing loss is hearing loss caused by disease of the inner ear, auditory nerve, or the central parts of the brain (brain stem or auditory cortex). The causes of damage to the auditory analyzer are quite diverse and heterogeneous. In this regard, the factors responsible for the development of hearing impairment in children, that is, the causes of hearing loss, depending on the moment of exposure, are divided into antenatal, intranatal and postnatal.Children with hearing impairments are characterized by disorders of the psycho-emotional sphere and are characterized by the presence of increased emotional excitability, irritability, motor disinhibition, and timidity. Asthenic manifestations are also noted: a decrease in working capacity, exhaustion of all mental processes, slowing down of perception, difLculty switching attention, a small amount of memory.